“It’s Challenging”: Pre-Service Teachers in Teaching Students at Islamic Elementary Level Post Covid-19 Pandemic - Khunaivi, Herman; Hidayah, Syarifatul Fitri (ELITE JOURNAL, 2023)
ABSTRACT Due to the Covid-19 pandemic, swift changes in the mode of instruction have caused teachers to face new challenges and situations in the classroom. These changes have resulted in new experiences for teachers to deal with. The purposes of this study were to explore how pre-service teachers prepared themselves in the teaching and learning process in the classroom and what made them challenging in teaching students at the Islamic elementary level. Through joining teaching practice at the Islamic elementary level directly, it made pre-service teachers challenged in doing such kinds of teaching and learning processes in handling the students in the classroom. To overcome these problems, the pre-service teachers employed such kinds of strategies for example Discovery Learning strategies, Contextual Teaching-Learning strategies, and utilizing the “Snake and ladder” and also “Beberan” Game Board as creative media in their teaching and learning process. The implication of this study was as pre-service teachers needed to develop an awareness of the teaching strategies for teaching students at the Islamic elementary level. Culling the appropriate strategies and media were needed in teaching the students at the Islamic elementary level to engage the students to activate joining in the classroom. Keywords: Pre-Service Teachers, Teaching Strategies, Islamic Elementary Students, Post Covid-19 Pandemic